Answer:
(1)7 (2)9 (3)6
Step-by-step explanation:
![\left|\begin{array}{c|cc}X&f(X)=X^2+7\\--&-----\\2&11\\3&16\\4&23\\5&32\\6&43\end{array}\right|](https://tex.z-dn.net/?f=%5Cleft%7C%5Cbegin%7Barray%7D%7Bc%7Ccc%7DX%26f%28X%29%3DX%5E2%2B7%5C%5C--%26-----%5C%5C2%2611%5C%5C3%2616%5C%5C4%2623%5C%5C5%2632%5C%5C6%2643%5Cend%7Barray%7D%5Cright%7C)
(1)The average rate of change between x=2 and x=5
![\dfrac{dy}{dx} =\dfrac{f(5)-f(2)}{5-2} =\dfrac{32-11}{3} =\dfrac{21}{3} =7](https://tex.z-dn.net/?f=%5Cdfrac%7Bdy%7D%7Bdx%7D%20%3D%5Cdfrac%7Bf%285%29-f%282%29%7D%7B5-2%7D%20%3D%5Cdfrac%7B32-11%7D%7B3%7D%20%3D%5Cdfrac%7B21%7D%7B3%7D%20%3D7)
(2)The average rate of change between x=3 and x=6
![\dfrac{dy}{dx} =\dfrac{f(6)-f(3)}{6-3} =\dfrac{43-16}{3} =\dfrac{27}{3} =9](https://tex.z-dn.net/?f=%5Cdfrac%7Bdy%7D%7Bdx%7D%20%3D%5Cdfrac%7Bf%286%29-f%283%29%7D%7B6-3%7D%20%3D%5Cdfrac%7B43-16%7D%7B3%7D%20%3D%5Cdfrac%7B27%7D%7B3%7D%20%3D9)
(3)The average rate of change between x=2 and x=4
![\dfrac{dy}{dx} =\dfrac{f(4)-f(2)}{4-2} =\dfrac{23-11}{2} =\dfrac{12}{2} =6](https://tex.z-dn.net/?f=%5Cdfrac%7Bdy%7D%7Bdx%7D%20%3D%5Cdfrac%7Bf%284%29-f%282%29%7D%7B4-2%7D%20%3D%5Cdfrac%7B23-11%7D%7B2%7D%20%3D%5Cdfrac%7B12%7D%7B2%7D%20%3D6)
Answer:
mc013-1.j pg
Step-by-step explanation:
The answer is A
The answer to this equation is 13ft squared
1.5% of 4,000$ is 60$ . 60$ times 3 years = 180$